Integrative Model of Work Direction, Work Understanding, And Work Enthusiasm: Moderation of Training Programs - Syahfira Aryani; Ezzah Nahrisah; Alvin Fahlevi (LPPPIPublishing, 2026)
This investigation seeks to ascertain the impact of work direction implementation on work understanding. To determine the impact of work direction implementation and work understanding on employee work enthusiasm partially. To assess the impact of work direction implementation on employee work enthusiasm through work understanding at PT. Swasana Sukses Bersama Medan. The research methodology employed in the present study is causal quantitative associative research, in which the method of data analysis employed is path analysis and MRA, and data processing will be carried out using SPSS. The results revealed that work direction implementation had a important impact and favorable on employee work enthusiasm, work understanding had a important impact and favorable on employee work enthusiasm, work direction implementation had a important impact and favorable on work understanding, work understanding mediated the impact of work direction implementation on employee work enthusiasm.